Factors associated with anxiety symptoms among medical laboratory professionals in Khobar: Single institution study - Althumairi, Arwa; Ayed AlOtaibi, Noot Mishal; Alumran, Arwa; Alrayes, Saja; Owaidah, Amani (Frontiers in Public Health, 2022)
Background A clinical professional has a challenging role during the coronavirus disease (COVID-19) pandemic in providing timely and accurate results with limited resources and a rapid increase in the number of samples to be tested. However, during the ongoing pandemic, the anxiety level of Medical Laboratory Professionals (MLT) has not been studied in Saudi Arabia within the hospital environment. Aim To determine the associated factors related with anxiety level of MLT at King Fahd Hospital of the University (KFHU) during the COVID-19 pandemic. Methods The study design was a cross-sectional quantitative study. Data were collected by administering a paper-based questionnaire that was distributed among MLT at KFHU. The questionnaire consisted of three sections. The first two sections were prepared by the researchers and included participant demographics and questions related to COVID-19. The third section used the Hamilton Anxiety Scale to assess anxiety levels. Result The study revealed that 70.4% of MLT showed no signs of anxiety, while 19.2% showed mild/moderate anxiety levels, and approximately 10.4% showed severe to extreme anxiety levels. In addition, a significant association between the anxiety level and difficulty breathing among MLT wearing personal protective equipment was observed. Moreover, a significant association between sex and anxiety level was identified. Females MLT had higher percentages of severe anxiety (12.8% vs. 5.1%) and mild/moderate anxiety (24.4 vs. 7.7%) than males. Conclusions Protecting the mental health status of MLT is an essential part of public health measures to fight the COVID-19 pandemic.